The effect of a competitive wrestling season on body weight, hydration, and muscular performance in collegiate wrestlers - Buford, T. W.; Rossi, S. J.; Smith, D. B.; O'Brien, M. S.; Pickering, C. (The Journal of Strength and Conditioning Research, 2006)
The purpose of the present investigation was to examine the effects of a collegiate wrestling season on body weight, hydration, and muscular performance. Twelve Division I collegiate wrestlers (mean ± SE; 20.75 ± 0.41 year) volunteered to participate in testing sessions during midseason and 3 weeks following the season. Testing consisted of weigh-in, providing a urine sample for hydration analysis, and a measure of isometric leg extension peak torque. Weight significantly increased (p < 0.05) following the completion of the competitive season. No significant change in urine specific gravity (p > 0.05) was observed. Muscular performance was affected by the season as peak torque (PT) and PT-to-body weight ratio increased significantly (p < 0.05). Following the collegiate wrestling season, augmentation in body weight and muscular performance of the wrestlers occurs without alterations in hydration status. Further research is warranted on what type of strength training program would most effectively reduce the decrements in strength associated with weight loss and the strain of a competitive season.